Dampak Partisipasi Anggaran, Tanggung Jawab Akuntansi dan Desentralisasi Fiskal terhadap Kinerja Manajerial Melalui Komitmen Organisasi pada Pelayanan Pemerintah Kota Palu - Syam Sawal Qamar; Agus Munandar (Syntax Literate, 2023)
To improve the company's effectiveness, it is essential to conduct an evaluation of managerial performance, particularly in the implementation of managerial functions. This study aims to analyze the impact of budgetary participation, accountability accounting, and fiscal decentralization on managerial performance through organizational commitment in the Palu City Government Department. The hypotheses were tested using SEM PLS with a sample of 100 respondents. The findings of the research indicate that accountability accounting and budgetary participationxdoxnotxhave a significant influence on managerial performance. However, fiscal decentralization and organizational commitment have a significant impact on managerial performance. Moreover, accountability accounting, budgetary participation, and fiscal decentralization have an effect on organizational commitment. Additionally, organizationalxcommitmentxmediates the relationship between accountability accounting, budgetary participation, fiscal decentralization, and managerial performance.